2021
DOI: 10.1155/2021/9924667
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends of Food Analysis, Safety, and Packaging

Abstract: Food is a basic necessity for life, growth, survival, and maintaining a proper body function. Rising food demand leads both producers and consumers to search for alternative food sources with high nutritional value. However, food products may never be completely safe. The oxidation reaction may alter both the physicochemical and immunological properties of food products. Maillard and caramelization nonenzymatic browning reactions can play a pivotal role in food acceptance through the ways they influence qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 195 publications
0
6
0
Order By: Relevance
“…In recent years, research has aimed at enhancing the qualitative parameters of apricot, and specific breeding programs have focused on the improvement of apricot flavor through determination of the roles played by principal acids and sugars, aiming to produce new cultivars with better traits such as good flesh taste, aroma, and firmness, high sugar content, big size and attractive fruit color, extensive harvesting period, and resistance to Sharka disease, as all local European cultivars are susceptible [9,10]. Fruit quality is fundamental for the acceptance of apricot cultivars by consumers [11], and this concept depends on sensory properties (appearance, texture, taste and aroma), nutritional values, chemical compounds, and mechanical and functional properties [12]. So, new apricot cultivars must be characterized by fruit quality attributes that satisfy consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research has aimed at enhancing the qualitative parameters of apricot, and specific breeding programs have focused on the improvement of apricot flavor through determination of the roles played by principal acids and sugars, aiming to produce new cultivars with better traits such as good flesh taste, aroma, and firmness, high sugar content, big size and attractive fruit color, extensive harvesting period, and resistance to Sharka disease, as all local European cultivars are susceptible [9,10]. Fruit quality is fundamental for the acceptance of apricot cultivars by consumers [11], and this concept depends on sensory properties (appearance, texture, taste and aroma), nutritional values, chemical compounds, and mechanical and functional properties [12]. So, new apricot cultivars must be characterized by fruit quality attributes that satisfy consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that beta-D-glucans are in the form of a random coil or in the form of an ordered structure, which depends on the available binding sites, and with the spatial organization of beta-D-glucans changing, there is higher or lower adsorption of toxic molecules. Carboxylic, amino, hydroxyl, and amide groups of proteins and carbohydrates found in the cell wall of beta-glucans are involved in the binding of metals to yeasts [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The project is coordinated by the Hellenic Mediterranean University, while participates include the University of Crete, the Hellenic Agricultural Organization DIMITRA or "ELGO-Dimitra", as well the Greek Foundation of Research and Technology (FORTH). One of our tasks is the determination and characterization of the actual LAB flora that can be potentially used as a starter for Xygalo Siteias.Furthermore, appropriate packaging solutions [29,30] could minimize quality changes in soft cheeses, resulting in an increased shelf life as well as quality maintenance. In due course, we will also search for new material with antimicrobial action, under the program "Sustainable food packaging based on essential oils in polymeric matrices", with the acronym 'NanoBioPack' with code MIS 5,056,214 and project code: T6ΥBΠ-00307, (project code HMU: 80746), which is implemented within the framework of the National Action "Aquaculture"-"Industrial Materials"-"Open Innovation in Culture" of the Operational Program "Competitiveness, Entrepreneurship and Innovation" (EPANEK) 2014-2020 and is co-financed by the European Regional Development Fund (ERDF).…”
Section: Discussionmentioning
confidence: 99%